THE EFFECT OF INQUIRY BASED LEARNING WITH SOCIOSCIENTIFIC ISSUES CONTEXT ON CRITICAL THINKING SKILLS AND SCIENTIFIC EXPLANATION - Intan Mahanani; Sri Rahayu; Fauziatul Fajaroh (Jurnal Kependidikan, 2019)
This study was aimed at investigating the application of inquiry learning in the context of socioscientific issues (SSI) influences students' skills in critical thinking and scientific explanation on the topic of reaction rates. This study was quantitative research used post test only control group design. A total of 90 students who were enrolled in the 3 classes from one public senior high school in Malang regency were selected as the research sample by convenience. The data of critical thinking ability were collected through critical thinking test. The data of scientific explanation were collected through scientific explanation test. The results of critical thinking test were categorized by Ennis’s critical thinking, while the results of scientific explanation test were categorized by SOLO taxonomy. The data were analysed quantitatively by statistical parametric. The result of One-Way ANOVA showed that there were significant differences in students' critical thinking skills and scientific explanation ability who were taught by inquiry with SSI learning, inquiry, and verification model. Students who were taught by inquiry with SSI learning had a higher average of critical thinking and scientific explanation skills than the students who were taught by inquiry and verification learning. PENGARUH PEMBELAJARAN INKUIRI BERKONTEKS SOCIOSCIENTIFIC-ISSUES TERHADAP KETERAMPILAN BERPIKIR KRITIS DAN SCIENTIFIC EXPLANATIONPenelitian ini bertujuan untuk menginvestigasi pengaruh penerapan pembelajaran inkuiri berkonteks socioscientific issues (SSI) terhadap keterampilan siswa dalam berpikir kritis dan scientific explanation pada topik laju reaksi. Penelitian kuantitatif dilakukan dengan posttest only control group design. Sampel penelitian berjumlah 90 siswa yang terbagi ke dalam 3 kelas dari satu SMA Negeri di Kota Malang yang dipilih menggunakan teknik convenience sampling. Data keterampilan berpikir kritis diperoleh dari tes keterampilan berpikir kritis. Data penjelasan ilmiah dikumpulkan dengan tes scientific explanation. Data kemampuan berpikir kritis dikategorikan menurut kategori berpikir kritis Ennis. Adapun data kemampuan scientific explanation siswa dikategorikan menurut taksonomi SOLO. One-Way ANOVA digunakan untuk menganalisis pengaruh perlakuan Hasil penelitian menunjukkan adanya perbedaan yang signifikan keterampilan berpikir kritis dan scientific explanation pada siswa yang dibelajarkan dengan pembelajaran inkuiri berkonteks SSI, inkuiri, dan verifikasi. Siswa yang dibelajarkan dengan pembelajaran inkuiri berkonteks SSI memiliki nilai rata-rata keterampilan berpikir kritis lebih tinggi dan lebih mampu membangun explanation hingga level tertinggi yaitu level extended abstract, dibandingkan dengan siswa yang dibelajarkan menggunakan pembelajaran inkuiri dan verifikasi.